Studies on the Kinetics and Mechanism of Oxidation of Nitrones by Pyrazolinium Dichromate in aqueous DMSO medium (Global Journal of Science Frontier Research, 2015)
The kinetics and mechanism of oxidation of N, α-diphenylnitrones by some substituted nitrones by Pyrazolinium dichromateyielding benzaldehyde and nitrosobenzene in aqueous dimethyl sulphoxidemedium have been investigated. First order dependence with respect to both [PyDC] and [NO]. The compound was prepared and purity of the oxidant was estimated by iodometric method. The reaction is fractional order with respect to [H + ]. Electron-releasing substituents increase the rate of the reaction and electron withdrawing substituents decrease the rate of the reaction. No polymerisation observed with acrylamide ruling out a free radical mechanism. There was no discernible effect with increasing in ionic strength but the rate of oxidation decreased with decreasing dielectric constant of the medium. Addition of MnSO 4 had a significant and acrylonitrile no effect on the reaction rate.
Keywords: N; α- diphenylnitrones; pyrazolinium dichromate; kinetics; isokinetic plot; entropy; enthalpy and rate constants